2021
DOI: 10.1177/2158244021989275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Public Awareness Campaign on Time to and Way of Hospital Admission After Stroke

Abstract: Public education campaigns are recommended to increase awareness for stroke. The effect of a public advertising and education campaign in an urban region in Germany was assessed and compared with a control region. We hypothesized that such a campaign would increase the number of patients being admitted by emergency medical services (EMS). A multimedia campaign and targeted education of health care professionals and the public was employed in Berlin during six consecutive months to disseminate knowledge about s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A recent study by Heuschmann et al evaluated a German campaign that took place in an urban region and compared it to a similar region without any campaign. They found that the proportion of patients admitted via EMS and within 2 h from symptom onset improved equally in both regions and concluded that the campaign had no effect 42 . However, the size and the budget of the campaign was unclear and some of the initiatives in the urban region could have influenced the public in the control region as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Heuschmann et al evaluated a German campaign that took place in an urban region and compared it to a similar region without any campaign. They found that the proportion of patients admitted via EMS and within 2 h from symptom onset improved equally in both regions and concluded that the campaign had no effect 42 . However, the size and the budget of the campaign was unclear and some of the initiatives in the urban region could have influenced the public in the control region as well.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the proportion of patients admitted via EMS and within 2 h from symptom onset improved equally in both regions and concluded that the campaign had no effect. 42 However, the size and the budget of the campaign was unclear and some of the initiatives in the urban region could have influenced the public in the control region as well. Some studies have found significant reductions in the prehospital delay after a campaign, for example, Chen et al, who conducted a controlled before-and-after study in China.…”
Section: Findings In Relation To Other Studiesmentioning
confidence: 99%
“…The SSS score ranges from 0 to 58; low score indicates severe stroke. In the analyses, we divided scores into minor (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58), moderate (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) and severe (0-25) stroke. 26 We adjusted for covariates in the multivariable regression analyses, as they were considered potential confounders.…”
Section: Variables and Statistical Analysesmentioning
confidence: 99%